Application of e-Marketing Tools at Keells Super, Sri Lanka - Chathuranga, W.M.N.; Shivany, S. (My University, 2020)
e- Marketing is a process that information technologies and digital platform tactical to support and execute to marketing activities, and a digital interactive technology used to deliver and communicate products to the target audiences. Since the emergence of e- Marketing applications, there are many organizations have it‘s as competencies for differentiation for strategic competitive advantages. Keells Super is a leading organization applying e-marketing as strategy for developing their achievements. This research is intending to identify how Keells super applies e-Marketing tools in its business context. A qualitative study was carried out to answer the research questions of this applied marketing research. Data were collected from 20 managers and 25 customers via in-depth interviews. Present study found thee-Marketing applications programs such as Social Media Shopping and Promotional (Face Book) Campaign- customer can join and know about executed promotions and information they want; Online shopping- quick purchasing orders and staff feedback to manage day to day life;Mobile SMS promotion campaign-based on customer mobile number short message services engage with customer as Nexus mobile loyalty program in which customer can become a member of Keels as Nexus Customer. And provide information about Seasonal Promotions; Keells Super Nexus Mobile: Customer can have solution for their issues related with Keels through the customer hotline. Under the Nexus Mobile Loyalty Program customers are registered in nexus in each mobile phone number. Findings shows that Applications of these e-marketing tools has created loyalty customer data base. According to the feedback from the customer, they enjoy the e-Marketing application particularly Nexus Mobile Loyalty program have encouraged them to stay with the company as loyal customersKeells Super, Sri Lanka continuously fine-tunes the application with the feedback from the customers. This research give practical implications as these e-Marketing tools can be applied as the delivery platform as well as the communication platform among the Sri Lankan consumers with the feedback and participation of them.
Keywords: e- Marketing tools; Face book; Mobile; Web site; Nexus mobile loyalty program